Chiang Rai United Football Club: provincial identity in the making - Bisma Putra Sampurna (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Football has become one of the most popular sports in Thailand. Yet, football in Thailand should not only be treated as a sport. Since 2009, Thailand professional football league no longer serves merely as a sporting competition. It serves as a space in which the power relations among actors takes place. The complex interplay of power relations among the provincial power has intensified the process of identity construction in the provincial area. The unique capability of football to institutionalize particular form of identity allows us to comprehend how the club and the fans construct their identity. Special attention is given to Chiang Rai United Football Club and its fans who located in Chiang Rai Province and Bangkok. The proposed arguments are that the construction of provincial identity is mediated by football club and provincial power; that professional football club and provincial power provides a space for the fans to exercising their identity politics; and the process of identity construction is being conducted by the football club and the fans.